Nanostructural Deformation Analysis of Calcium Silicate Hydrate in Portland Cement Paste by Atomic Pair Distribution Function - Hiroshi Suzuki; Sungchul Bae; Manabu Kanematsu (Advances in Materials Science and Engineering)
The deformation of nanostructure of calcium silicate hydrate (C-S-H) in Portland cement (PC) paste under compression was characterized by the atomic pair distribution function (PDF), measured using synchrotron X-ray diffraction. The PDF of the PC paste exhibited a unique deformation behavior for a short-range order below 2.0 nm, close to the size of the C-S-H globule, while the deformation for a long-range order was similar to that of a calcium hydroxide phase measured by Bragg peak shift. The compressive deformation of the C-S-H nanostructure was comprised of three stages with different interactions between globules. This behavior would originate from the granular nature of C-S-H, which deforms with increasing packing density by slipping the interfaces between globules, rearranging the overall C-S-H nanostructure. This new approach will lead to increasing applications of the PDF technique to understand the deformation mechanism of C-S-H in PC-based materials.